The Influence of Content Marketing on Consumer Preferences for Healthy and Sustainable Food Products in Soppeng Regency - Surianti Surianti; Andi Nurhidayati; Asnia Minarti; Puji Rahmah; Amrial Amrial (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
The increasing consumption of healthy and sustainable food products has become a strategic issue in supporting regional food security, including in Soppeng Regency. Amid changes in consumer behavior and the dominance of digital media, content marketing has emerged as an effective marketing communication strategy to build consumer knowledge, interest, and preferences toward healthy food products. However, understanding of the extent to which content marketing influences consumer preferences for sustainable food products in Soppeng remains limited. This study aims to analyze the influence of content marketing elements, including information quality, content creativity, message consistency, and source credibility, on consumer preferences for healthy and sustainable food products. This study employed a quantitative approach using a survey design. Data were collected through questionnaires distributed to consumers who had consumed or followed promotions of healthy food products in Soppeng Regency. The analysis technique used was multiple linear regression to examine the influence of content marketing variables on consumer preferences. The results of the study indicate that content marketing has a significant influence on consumer preferences for healthy and sustainable food products in Soppeng Regency